Sexuality of Colonized Subjects, a Postcolonial Analysis - Anjani Salim, Siti Amira; Dwiningtyas Sulistyani, Hapsari; Lukmantoro, Triyono (Interaksi Online, 2024)
This study explores @coolestkev's disruptive strategy of sexualizing Dutch colonization on TikTok through feminist rhetorical criticism and postcolonial analysis. The goal is to understand how this approach reinforces or challenges traditional gender norms and reflects postcolonial power structures. The results show that @coolestkev strengthens traditional gender norms and romanticizes the colonial past, while response videos from other creators present strong counter-narratives through nationalism and collectivism. This analysis reveals the complexities of identity in colonized societies, including internalized heterosexism and social pressures surrounding masculinity